Effect of Supplementation of Combination of Prebiotic and Acidifier on Performance of Broiler Chicken - Khemalapure, Sachin; Ramteke, Bhushan; Gadegaonkar, Ganesh; Karambele, Narendra; Jagadale, Suresh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was undertaken to evaluate the effect of supplementation of prebiotics (Mannanoligosaccharide, MOS) and acidifiercombination on the performance of broilers. The feeding trial was conducted on 135-days-old ‘Cobb-400’ broiler chicks for a period ofsix weeks. The day-old broiler chicks were randomly divided into three equal groups viz. T0, T1 and T2 comprised 45 birds each, furthersubdivided into three replicates of 15 birds each. Group T0 served as control and received a standard broiler diet. The birds in groups T1and T2 were fed diets containing prebiotic (MOS) and acidifier combination @ 0.05% and 0.75%, respectively. The birds from group T1received diet containing a prebiotic (MOS) and acidifier combination @ 0.05% of feed. The birds from group T2 received a diet containinga prebiotic (MOS) and acidifier combination @ 0.075% of the feed. The final live body weight and total weight gain of birds of T1 groupwas significantly (p
Keywords: Acidifier; Broiler; Combination, Performance Poultry Prebiotic